Republic of Poland : Review Under the Flexible Credit Line Arrangement: Staff Report and Statement by the Executive Director. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper reviews Poland's economic performance under the Flexible Credit Line Arrangement. Economic growth in Poland is expected to slow in 2012, given the deteriorating outlook for the euro area. Risks are on the downside, mainly reflecting the possibility of spillovers from escalating financial and sovereign stress in the rest of Europe. The authorities have continued to take steps to mitigate the effects of external shocks. Substantial fiscal consolidation is under way; sound monetary policy is helping inflation decline toward the target; and measures have been taken to safeguard financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet